2010
DOI: 10.1039/c002314k
|View full text |Cite
|
Sign up to set email alerts
|

Chirality of and gear motion in isopropyl methyl sulfide: A Fourier transform microwave study

Abstract: Isopropyl methyl sulfide (CH(3))(2)CHSCH(3) was investigated by Fourier transform microwave spectroscopy. Two rotational isomers gauche and trans were detected. The rotational spectra of gauche were found fit to an asymmetric rotor pattern, except for being split by the internal rotation of CH(3) attached to S with the potential barrier V(3) of 601.642 (65) cm(-1) and for exhibiting the effect of tunneling between the two equivalent gauche forms in a few high-K transitions. The tunneling was discussed from a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…An interesting case is methyl isopropyl ether, for which Nakagawa et al reported a torsional barrier of 603 cm 1 for the methoxy methyl group O-CH3 determined by fitting the doublet structure observed for some transitions [57], which is unusually low for such methyl group and quite similar to the value of 601.642(65) cm 1 obtained for the gauche conformer of methyl isopropyl sulfide with comparable structure [58]. Currently, no conclusive statement could be made to explain the origin of different values of methyl torsional barrier in thioethers and ethers with the small number of available studies.…”
Section: Thioethers Vs Etherssupporting
confidence: 54%
“…An interesting case is methyl isopropyl ether, for which Nakagawa et al reported a torsional barrier of 603 cm 1 for the methoxy methyl group O-CH3 determined by fitting the doublet structure observed for some transitions [57], which is unusually low for such methyl group and quite similar to the value of 601.642(65) cm 1 obtained for the gauche conformer of methyl isopropyl sulfide with comparable structure [58]. Currently, no conclusive statement could be made to explain the origin of different values of methyl torsional barrier in thioethers and ethers with the small number of available studies.…”
Section: Thioethers Vs Etherssupporting
confidence: 54%
“…In the case of closely located two methyl groups in the same molecule, a specially correlated methyl rotation which is called geared methyl rotation has been reported. In a 9-methyltriptycene derivative, a raising barrier for the isolated rotation of the two methyl groups obtained by 1 H NMR line shape indicated that the two methyl groups in space could be considered as a pair of gear . Methyl groups in hexamethyl benzene have been reported to undergo a geared disrotatory motion in the solid state. , It is important to note that the geared motions in methyl groups have been reported in the densely located methyl groups in the molecules and tightly packed in the solid state.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, harmonic frequency calculations were performed to verify the nature of the stationary points. This method and basis set was chosen empirically, as we know from experience that it yields rotational constants that usually agree within 1% of the experimental constants. , It is therefore widely used in the microwave spectroscopic community. , The geometry of conformers I and II observed in the molecular beam was also optimized again at different levels of theory including HF, MP2, and DFT methods in order to check for convergence. Finally, different transition states of dihydro-2-methyl-3-thiophenone were optimized to understand the intramolecular conversion between the two conformers at the MP2/6-311++G­(d,p) level of theory.…”
Section: Experimental and Computational Sectionmentioning
confidence: 99%
“…16,17 It is therefore widely used in the microwave spectroscopic community. 18,19 The geometry of conformers I and II observed in the molecular beam was also optimized again at different levels of theory including HF, MP2, and DFT methods in order to check for convergence. Finally, different transition states of dihydro-2-methyl-3-thiophenone were optimized to understand the intramolecular conversion between the two conformers at the MP2/6-311++G(d,p) level of theory.…”
Section: ■ Introductionmentioning
confidence: 99%